1997
DOI: 10.1046/j.1365-2141.1997.1272941.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic selection of CD34+peripheral blood stem cells for autografting in patients with breast cancer

Abstract: Summary. Contamination of transplants with tumour cells may contribute to relapse after peripheral blood stem cell transplantation (PBSCT). We studied the feasibility of CD34 þ cell selection from blood-derived autografts obtained following G-CSF-supported cytotoxic chemotherapy in a group of 25 patients with breast cancer (10 with high-risk stage II/III and 15 with stage IV without bone or bone marrow involvement).Using immunomagnetic beads (Isolex 300 SA, Baxter) CD34 þ cells were enriched and released by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…[10][11][12] Preclinical studies have suggested several clinical applications of highly purified CD34 ϩ cells, including tumour cell purging. Enrichment of CD34 ϩ cells has been proven to deplete tumour cells from autografts, [13][14][15][16][17][18] and is necessary for ex vivo expansion of progenitor cells. Furthermore, highly purified CD34 ϩ cells are essential for optimal cytokine-mediated expansion and differentiation in short-term culture.…”
mentioning
confidence: 99%
“…[10][11][12] Preclinical studies have suggested several clinical applications of highly purified CD34 ϩ cells, including tumour cell purging. Enrichment of CD34 ϩ cells has been proven to deplete tumour cells from autografts, [13][14][15][16][17][18] and is necessary for ex vivo expansion of progenitor cells. Furthermore, highly purified CD34 ϩ cells are essential for optimal cytokine-mediated expansion and differentiation in short-term culture.…”
mentioning
confidence: 99%
“…Chymopapain has been shown to modify the CD34 + cell surface. 5,36 In contrast, peptide release has been found by scanning electron microscopy to result in a highly homogeneous cell population with complete surface integrity and free of magnetic beads. 18 Murine MoAbs recognize different epitopes of the CD34 sialoglycoprotein.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5] Among the potential benefits of CD34 + cell enrichment for patients with malignant disease is the concomitant depletion of tumor cells in autologous transplant grafts. [5][6][7][8] CD34 antigen has been shown to be present primarily on progenitor and stem cells, and is not found on mature blood cells or non-Hodgkin's lymphoma, myeloma or most solid tumor cells. 9 In allogeneic transplantation, CD34 selection can provide hematopoietic cells that support hematological recovery and can serve to reduce the number of T cells in transplant grafts.…”
mentioning
confidence: 99%
“…With the 103 objective, tight square packing of the smaller HSC cells with low (0.1%) proportion of contaminant cells, and fast, dynamic ablation implemented in parallel with scanning, the 175 million cells required for one adult patient (21,22) would be processed in as little as 1 h, or as fast as about 48,600 cells/s. At lower magnification, Cyntellect (San Diego, CA) has reported microscope image-based ablation at a rate of 100,000 cells/s with as many as 2,000 cells/s (or 2%) contaminant cells (4).…”
Section: Discussionmentioning
confidence: 99%